(untitled) (Географический вестник=Geographical bulletin, 2017)
Предложен подход к выявлению некоторых показателей в структуре интегрального индикатора качества жизни населения, рассчитанного для конкретной территории, удельный вес которых в наибольшей степени объясняет его дисперсию. Исследование проведено на примере Пермского края. THE ANALYSIS OF ESTIMATION CRITERIA OF REGIONAL SPATIAL DEVELOPMENT The article proposes an approach to identify some indicators in structure of the integral indicator of life quality (calculated for Perm Region) and to define the proportion of their weights in integral indicator’s variance explanation. Such approach may be applied in practice of regional policy and spatial development.